YAP/Hippo Pathway and Cancer Immunity: It Takes Two to Tango - Dimitrios Matthaios; Maria Tolia; Davide Mauri; Konstantinos Kamposioras; Michalis Karamouzis (Biomedicines, 2021)
Hippo pathway with its main molecule YAP is a crucial pathway for development, tissue homeostasis, wound healing, tissue regeneration, and cancer. In this review, we discuss the multiple effects of the YAP/Hippo pathway in the immune system and cancer. We analyzed a series of effects: extracellular vesicles enhanced immunity through inhibition of LATS1/2, ways of modulation of the tumor microenvironment, YAP- and TAZ-mediated upregulation of PDL1, high expression of YAP and PDL1 in EGFR-TKI-resistant cells, enhanced YAP activity in inflammation, and the effect of the Hippo pathway on T cells, B cells, Tregs, macrophages, and myeloid-derived suppressor cells (MDSCs). These pleiotropic effects render the YAP and Hippo pathway a key pathway for exploitation in the future, in order to enhance our immunotherapy treatment strategies in oncology.